CATALASE AND GLUTATHIONE-S-TRANSFERASE ACTIVITY IN DIFFERENT TISSUES OF FRESHWATER CATFISH CLARIAS GARIEPINUS ON EXPOSURE TO CADMIUM - SUMIT ROSE,; S.VINCENT,; B.MEENA, (International Journal of Pharma and Bio Sciences, 2014)
Pollution by heavy metals is a serious problem due to their toxicity and ability to accumulate in the biota. In vivo effects of Cadmium (Cd) levels of expression on antioxidant enzymes such as Catalase (CAT) and Glutathione-S-transferase (GST) were investigated in liver, kidney, gill and brain tissues of freshwater Catfish, Clarias gariepinus. CAT is a common antioxidant enzyme which breaks down hydrogen peroxide into oxygen and water and restricts the accumulation of carbon dioxide bubbles in the blood. is produced naturally in almost all living organisms. CAT levels were measured using spectrophotometrically at 570 nm. Activity of GST which plays an important role in the detoxification of xenobiotics was studied along with Cd. The GST levels were measured using spectrophotometrically at 340 nm. Hence CAT and GST enzymes can be considered as a sensitive bioindicator of the antioxidant defense system.